Market Orientation, Digital Marketing Capabilities, and Product Innovation on Competitive Advantage through Customer Engagement: Evidence from the Creative Economy Sector in Indonesia - Sucidha, Irma; Diany, Adista Anjar; Irayana, Ika (The Eastasouth Management and Business, 2025)
This study examines the influence of market orientation, digital marketing capabilities, and product innovation on competitive advantage through customer engagement in the Indonesian creative economy sector. A quantitative approach was employed, with data collected from 250 respondents using a five-point Likert scale. Structural Equation Modeling–Partial Least Squares (SEM-PLS 3) was used for data analysis. The results demonstrate that market orientation, digital marketing capabilities, and product innovation significantly enhance customer engagement, which in turn strongly contributes to competitive advantage. Customer engagement also mediates the relationships between these strategic factors and competitive advantage, emphasizing its role as a critical pathway to sustainable competitiveness. The findings highlight the importance of aligning market-oriented strategies, leveraging digital platforms, and fostering continuous innovation to build stronger customer relationships and long-term market advantage. The study contributes to both academic understanding and managerial practices in strengthening the creative economy sector in Indonesia.